Hidden hunger and diabetes care - Sanjay Kalra; Madhur Verma; Nitin Kapoor (Journal of the Pakistan Medical Association, 2023)
hunger, or micro- nutrient deficiency, and its link with diabetes care. It provides simple tools to help diabetes care providers suspect and identify micronutrient deficiency in their clinic. The authors highlight the need to tackle the third frontier of malnutrition - micronutrient deficiency, and add a third component -electrolyte and fluid balance, to the definition of hidden hunger. Keywords: Diet, nutrition, neurotropic vitamins, micronutrients, iron, calcium, vitamin D, iodine